PTHrP potentiating estradiol-induced vitellogenesis in sea bream (Sparus auratus, L.) - Bevelander, G. S. (2014)
n fish, vitellogenin is an important nutritional precursor protein produced solely in the liver and released into the blood where it binds calcium. In the gilthead sea bream (Sparus auratus) 17beta-Estradiol (E2) plays an important role in the synthesis of vitellogenin, but also the pituitary hormones prolactin (PRL) and growth hormone (GH) can stimulate vitellogenin induction in fish. Considering the emerging involvement of PTHrP in fish calcium metabolism and the importance of calcium regulation in reproduction, we investigated the possible role of PTHrP in vitellogenesis. E2-naïve and E2-primed sea bream hepatocytes were used in an in vitro primary hepatocyte culture and stimulated with a recombinant sea bream PTHrP (sbPTHrP) to establish the contribution of sbPTHrP alone or in combination with E2 to the regulation of hepatic vitellogenin synthesis. Hepatocytes stimulated solely with sbPTHrP were not affected in their vitellogenesis. However, in hepatocytes stimulated with E2 in combination with sbPTHrP a higher vitellogenin production was seen than with E2 alone. It is concluded that sbPTHrP has a potentiating effect on estradiol stimulation of vitellogenin production by sea bream hepatocytes. The sea bream provides a unique model where vitellogenesis regulation can be studied on E2-naïve liver cells, both in vivo and in vitro.